Constitution (Fundamental Law) of the Uzbek Soviet Republic. As amended by the Supreme Soviet of the Uzbek S.S.R., on June 25, 1948, on the recommendations of the Draftin Commission (Moscow, 1949)
Foreign Languages Publishing House.